Approximation of Continuous Functions of Low Smoothness by de la Vallee-Poussin Operators - Rukasov, V. I.; Silin, E. S. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study some problems of the approximation of continuous functions defined on the real axis. As approximating aggregates, the de la Vallee-Poussin operators are used. We establish asymptotic equalities for upper bounds of the deviations of the de la Vallee-Poussin operators from functions of low smoothness belonging to the classes \(\hat C^{\bar ψ } \mathfrak{N}\).